DEVELOPMENT OF COMMUNICATIVE QUALITIES OF EDUCATIONAL INSTITUTION TEACHERS IN THE PROCESS OF SPORTS AND MASS ACTIVITIES (Physical Culture and Sport: Scientific Perspective, 2025)
The article examines the significance of communicative competence for the effective performance of educators in modern educational institutions. Special attention is given to the issue of developing the communicative qualities of physical education teachers in the context of organizing sports and mass activities. Contemporary pedagogical practice requires teachers not only to possess professional knowledge and skills but also to demonstrate a high level of communicative competence in educational activities. This is particularly relevant in the sphere of sports and mass event organization, where interaction with various social groups (students, parents, colleagues, school administration, sponsors, etc.) is essential.The study highlights that effective communication enhances students' motivation, increases their engagement, and contributes to achieving high results in both sports and academics. The role of effective communication in the structured work with students is explored, with a focus on the importance of motivation and interaction in shaping a teacher's leadership qualities. Other crucial components of communicative competence in physical education teachers are identified and analyzed, including psychological resilience, empathy, pedagogical tact and speech culture, public speaking and constructive dialogue skills, active listening and tolerance, argumentation and persuasiveness, flexibility and adaptability, as well as digital communicative competence.The article also reviews contemporary methodologies for improving communication skills and their impact on the effectiveness of the educational process, student motivation, and the formation of a positive learning environment. To improve teachers' communicative competence, the study proposed several methods for developing communicative skills.
Keywords: communicative competence; speech culture; communicative qualities; pedagogical communication; pedagogical tact; verbal communication; non-verbal communication; business communication; sports and mass activities